Peningkatan Hasil Belajar Peserta Didik Tema Ekosistem Melalui Media Power Point Di Kelas V - Regi Gunawan (Universitas Sebelas Maret, 2020)
In general, the purpose of this research is to improve the learning of ecosystem themes of students in grade V of SD Negeri kutasari 05. while the special goal is to improve the learning results of the Ecosystem Theme using power point media. Class Action Research (PTK) conducted in three cycles, each cycle consists of planning, implementation, observation, and reflection stages. The subject of this study is students of Grade V SD Kutasari 05 Cipari District Cilacap District in the 2020/2021 school year which numbered 16 students. Data collection techniques using using tests. This research shows that the use of power point media can improve the learning results in thematic learning of students in Grade V SD Kutasari 05 years of study year 2020/2021 as evidenced by the percentage of completeness of learning results in cycle I by 72.36 %, cycle II by 90.1 %, and cycle III reaching 100%.